DNA-utilization loci enable exogenous DNA metabolism in gut Bacteroidales - Deepti Sharan; Agnieszka Nurek; Joshua Stemczynski; Kristof Turan; Alexander S. Little; Michael J. Coyne; Mary McMillin; Ashley M. Sidebottom; Laurie E. Comstock; Samuel H. Light (Proceedings of the National Academy of Sciences, 2025)
The human gut microbiome plays a central role in nutrient metabolism, yet the fate of exogenous nucleic acids within this ecosystem remains poorly understood. Here, we show that multiple Bacteroidales species efficiently metabolize exogenous DNA, with Bacteroides thetaiotaomicron converting it into the deaminated nucleobases uracil and xanthine. Using genetic and biochemical approaches, we identify ddbABCDEF , a six-gene locus encoding secreted nucleases and an outer membrane transporter, essential for exogenous DNA metabolism in B. thetaiotaomicron . Colonization of gnotobiotic mice with ddbABCDEF mutants reveals that this pathway significantly alters nucleobase pools in a gnotobiotic mouse model. Comparative genomic analyses demonstrate that ddbABCDEF is evolutionarily related to a natural transformation system present in Bacteroidota and has diversified into four distinct subtypes, each linked to unique DNA-processing activities in closely related gut Bacteroidales strains. These findings thus expand our understanding of DNA metabolism in the gut microbiome and reveal a distinctive pathway for nucleobase production with implications for host–microbe interactions.